Patternmaking with stretch knit fabrics - Cole, Julie (Julie Christine) (Fairchild Books, 2016)
"With hundreds of step-by-step illustrations and instructions and a user-friendly, stay-flat format, Patternmaking with Stretch Knit Fabrics provides emerging fashion designers with comprehensive information on how to draft patterns for popular cut and sew knits and stretch fabrics such as jersey and spandex. Cole explains the basics of stretch fabrics, how the stretch ratio impacts the design and how to correctly identify the type of knit. Technical drawing with step-by-step instructions guide the student to draft slopers and patterns using the principles of pattern drafting. Color accents highlight pattern markings to differentiate steps and clear photographs feature sewn garment samples and completed muslin patterns. The text begins with an introduction to working with knits and how to gauge the stretch capacity of fabrics. Grading instructions will guide students to create a set of Top and Hip Foundations for each of the four stretch categories of knits. Information is included on basic stitching of stretch knit fabric in order to construct test-fit garments. The author introduces a unique, simplified approach to drafting slopers using a hip and top foundations and provides information on converting, drafting, grading and reducing patterns for proper fit. The book proceeds to drafting slopers and patterns for tops, dresses, jackets and cardigans, skirts, pants, lingerie, and swimwear.The text is ideal for students with basic design, patternmaking and sewing skills at aan intermediate level for any course in which students design and draft patterns for knits. In addition the text could be used in a more general design course that incorporates both knits and woven fabrics"-- Provided by publisher.